The The impact of credit relaxation policies on sustainability performance of MSMEs - Lili Supriyadi; Supriyono; Hanifah Rizqy Arian (Enrichment : Journal of Management, 2023)
This research should explore the mechanisms through which credit relaxation policies influence sustainability performance and the conditions under which these policies are most effective during the pandemic covid-19, the most crisis MSMEs are Facing. This research is very urgent for elevate government policy with continuous improvement, especially for credit relxation policy. This research focuses on the impact of credit relaxation policies on the sustainability performance of MSMEs. Data analysis of 123 respondents was conducted using smart-PLS03 software. Research results show that the cost relaxation program, directly and indirectly, affects SMEs'SMEs' sustainability performance. Furthermore, various relaxation programs significantly affect SMEs' sustainability performance and have the highest contribution. The finding of the credit relaxation policy positively influences the sustainability performance of MSMEs in Indonesia, especially in the Jabodetabek area. This means that the better the credit relaxation policy set by the government during the pandemic, the more sustainable performance of MSMEs, especially in Indonesia, can be encouraged.